Implementation Of Minister Of Finance Regulation Number 168 Of 2023 Regarding Individual Taxpayer Compliance As An Effort To Streamline State Revenue (Case Study: Pt. Indobismar In Surabaya) - Pompong Budi Setiadi; Kurniawan Fiki; Sri Rahayu (UNIVED Press, 2025)
The government continues to innovate in tax policies to increase state revenue, one of which is PMK No. 168 of 2023, which regulates PPh 21 using an average effective tax rate. The objective of this study is to examine the execution of this policy at PT. Indobismar, evaluate its impact on state revenue, and examine its effect on individual taxpayer compliance. A quantitative approach was employed using a survey method through questionnaires distributed to 82 respondents selected using a saturated sampling technique. Data analysis was conducted using the SEM-PLS method to examine the relationships between latent variables and assess the effectiveness of policy implementation. The findings indicate that the implementation of PMK No. 168 of 2023 has been effective, positively impacting state revenue and improving individual taxpayer compliance in fulfilling their tax obligations. This policy plays a key role in establishing a more organized and predictable tax system, which in turn facilitates greater understanding and compliance with tax obligations among taxpayers. Additionally, the application of an average effective tax rate provides clarity and fairness in tax calculations, reducing ambiguity and increasing taxpayer confidence in the tax system. Overall, PMK No. 168 of 2023 is considered an important step toward a more transparent, efficient, and easily understandable tax regulation framework.